2019
DOI: 10.3390/en12142744
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Impedance Inversion Using Gaussian Metropolis–Hastings Sampling with Data Driving

Abstract: The Markov chain Monte Carlo (MCMC) method based on Metropolis–Hastings (MH) sampling is a popular approach in solving seismic acoustic impedance (AI) inversion problem, as it can improve the inversion resolution by statistical prior information. However, the sampling function of the traditional MH sampling is a fixed parameter distribution. The parameter ignores the statistical information of AI that expands sampling range and reduces the inversion efficiency and resolution. To reduce the sampling range and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…By comparing conventional GBM image with the corrected reflectivity image, we found that the image after correction has more balanced amplitudes in both the shallower and the deeper parts of the model, as well as more abundant wavenumber contents. We chose a local part of the model to show the quantitative im- Next, we implemented conventional GBM to produce the subsurface image and then performed the correction to produce a broadband reflectivity using Equation (5). The image from the conventional GBM and the corrected image using the proposed method are shown in Figure 3a,b, respectively.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing conventional GBM image with the corrected reflectivity image, we found that the image after correction has more balanced amplitudes in both the shallower and the deeper parts of the model, as well as more abundant wavenumber contents. We chose a local part of the model to show the quantitative im- Next, we implemented conventional GBM to produce the subsurface image and then performed the correction to produce a broadband reflectivity using Equation (5). The image from the conventional GBM and the corrected image using the proposed method are shown in Figure 3a,b, respectively.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Acoustic impedance (AI), as a basic physical parameter, is defined as the product of density and velocity, which plays a key role to connect the surface seismic data to the subsurface model [2,3]. Therefore, the broadband AI imaging is crucial for seismic interpretation and beneficial to reservoir predication [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, inversing AI from seismic data is significant research. In the past decades, several methods were proposed to solve this problem [4]- [6]. The pro-stack AI inversion is a popular one as it can transform the inversion problem to a linear optimization problem which can be solved easily [7]- [9].…”
Section: Introductionmentioning
confidence: 99%